BIOMEDICAL INDICATORS OF PRE-COMPETITIVE STRESS IN FEMALE AND MALE JUDO PLAYERS - Mroczkowska, Helena; Supiński, Jan; Litwiniuk, Artur; Obmiński, Zbigniew (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the present paper is to monitor changes of selected mental and physiological stress indicators in both female and male sportsmen in the subsequent days prior to an International Judo Tournament in Poland and on the competition day. The study included 9 men and 9 women, participants of the training camp that ended with a tournament. Every morning, on the three consecutive days preceding the competition (day -3, -2, -1) and on the competition day (day 0) capillary blood was sampled to determine serum cortisol (C) and testosterone (T) levels, then the subjects assessed their night sleep quality (SQ) with the use of a 5-point Likert scale, and perceived anxiety using the State-Trait Anxiety Inventory questionnaire by Spielberger (STAI - Polish version). SQ insignificantly deteriorated, and C and anxiety levels increased with the time to event. The inter-group analysis for the entire period showed higher scores in average anxiety and higher average level of C in women than men. The relative changes in these biomarkers could indicate higher pre-competitive stress in women, however without taking into account the sports class of the opponents individually for each of the groups one cannot imply gender-specific susceptibility to stress as a general principle.